Cittadini, dibattiti pubblici e legittimazione procedurale. Un early assessment dei dibattiti realizzati nel contesto del PNRR (agosto 2022) - Moro, Giovanni (Studi Politici, 2022)
The article is an early assessment of the first six public debates implemented in Italy in 2022, on the base of the documentation that was publicly available in August 2022. The debates have taken place in the context of the Next Generation EU program and in the framework of the public policy defined at national level in 2016, aimed at achieving the throughput legitimacy of big public works thanks to the involvement of the citizenry in discussing the defined projects. The debates, regarding road and rail works, are analyzed taking into consideration the punctual remarks and proposals coming from civic organizations and initiatives as well as the emerging criticalities of the public debates on the citizens’ side. In conclusion, risks of perverse effects in the implementation of the policy are highlighted and discussed.